PENGARUH FIRM SIZE, LEVERAGE, DAN INVESTMENT OPPORTUNITY TERHADAP CASH HOLDING - Alexandra Monica, Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This research aims to determine the effect of firm size, leverage and investment opportunity on cash holding at manufacturing companies listed on the Indonesian Stock Exchange in 2015-2017. The research uses a sample of 30 companies each year (90 observations). The method of analysis used is multiple regression analysis with SPSS version 23. The results of the research with 5 % significant level shows that firm size has positive effect on cash holding. Leverage has negative effect on cash holding. Investment opportunity doesn’t effect cash holding.